Penerapan Metode Take and Give dalam Meningkatkan Keterampilan Sosial Peserta Didik pada Kurikulum Merdeka - Nasrodin Nasrodin; Riza Faishol; Ainul Ikrom (INCARE, International Journal of Educational Resources, 2024)
The Independent Curriculum provides freedom to teachers and students in the learning process by focusing on the development of holistic competencies that include cognitive, affective, and psychomotor aspects. This take and give learning method is in line with the principles of the Independent Curriculum. This method emphasizes active and collaborative interaction between learners. This study aims to explore the application of the take and give method in learning the Qur'an Hadith at MTs Al-Azhar Sempu Banyuwangi to improve students' social skills. The social skills in question include communication, cooperation, empathy, and problem-solving, which are often less accommodated in conventional learning methods. This research uses a qualitative approach with a case study type. Data collection is carried out through observation, interviews and documentation, then the data is analyzed with the stages of data collection, data condensation, data display, and conclusions drawing/verifying. Checking the validity of the data using triangulation of sources and methods. The results of the study show that the take and give method is effective in improving students' social skills through improving communication skills, cooperation, and empathy, as well as applying the values of the Qur'an and Hadith in daily life. The contribution of this research to the development of a more holistic learning method and relevant to the principles of the Independent Curriculum. The take and give method is expected to be an innovative method to improve students' social skills.